English-induced changes to urban colloquial Hindi lexicon and structure. mixed speech as a mode of discourse - Borowiak, Tomasz (Lingua Posnaniensis, 2012)
This article aims at describing some of the lexical and grammatical innovations observed in Hindi as a result of English impact. We investigate some crucial aspects of English noun borrowing and further along discuss some other phenomena that occur in Hindi due to the language contact, e.g. preposition transfer and hybridization. The data for this research consists of internet newspaper excerpts, samples from Indian film and radio speech. We try to show that English influence has far reaching effects on Hindi lexicon and structure. The conclusion to be drawn from the present investigation is that the intense interaction between English and Hindi may be the initial step towards the creation of an interlanguage located somewhere between the two languages in question.